A Pengaruh Model Pembelajaran Project Based Learning Menggunakan Metode Inquiry Terhadap Kemampuan Pemahaman Konsep Siswa Kelas VII SMP Negeri O Mangunharjo: Pengaruh Model Pembelajaran Project Based Learning Menggunakan Metode Inquiry Terhadap Kemampuan Pemahaman Konsep Siswa Kelas VII SMP Negeri O Mangunharjo - Budiarti, Eka; Fitriyana, Nur; Rosalina, Elya (Jurnal Pendidikan Matematika RAFA, 2021)
This study aims to determine the effect of the Project Based Learning (PjBL) learning model by using the Inquiry method on the concept comprehension ability of Grade VII students of O Mangunharjo Middle School in 2019/2020. The research method used is pure experimental form. 154 students and the sample is class VII.A as an experimental class and VII.E as a control class. Collecting data in research using tests in the form of a matter of description. Data collected were analyzed using t-test at the significance level α = 0.05. Based on the results of the t-test analysis at a significant level, it can be concluded that there is a significant influence on the Project Based Learning (PjBL) learning model by using the Inquiry method on the ability of concept understanding of seventh grade students of O Mangunharjo Middle School in 2019/2020. The average score of the ability of understanding the concept of the experimental class was 33.13 and the control class was 27.74. Keywords: Project Based Learning Model, Inquiry Method, Concept Understanding